A revision of the Anthaxia (Haplanthaxia) dispar Kerremans species-group (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2020)
The taxonomic revision of the Anthaxia (Haplanthaxia) dispar Kerremans, 1898 species-group. Definition of the species-group and descriptions of three new species: Anthaxia (Haplanthaxia) aethiopica sp. nov. (Ethiopia), A. (H.) caerulea sp. nov. (Democratic Republic of the Congo) and A. (H.) occidentalis sp. nov. (Benin, Burkina Faso, Ivory Coast, Senegal, Sierra Leone, Togo). New species are described, illustrated and compared with other species of the species-group. Anthaxia (H.) komareki Obenberger, 1931 is removed from the synonymy of A. (H.) pilifrons Kerremans, 1898 and it is treated as a separate species. New synonymy is suggested: A. (H.) dispar Kerremans, 1898 = A. (H.) hyperlasia Obenberger, 1928, syn. nov. All species are keyed and the questionable taxonomic position of A. (H.) vulpes Théry, 1930 is briefly discussed.